Natural plant-derived polysaccharides targeting macrophage polarization: a promising strategy for cancer immunotherapy - Wei, Jingyang; Dai, Yanpeng; Zhang, Ni; Wang, Zijian; Tian, Xinchen; Yan, Tinghao; Jin, Xiaohan; Jiang, Shulong (Frontiers in Immunology, 2024)
Tumor associated macrophages (TAMs) are the predominant innate immune cells in the tumor microenvironment (TME). Cytokines induce the differentiation of macrophages into distinct types of TAMs, primarily characterized by two phenotypes: M1-polarized and M2-polarized.Cancer growth is suppressed by M1-polarized macrophages and promoted by M2-polarized macrophages. The regulation of macrophage M1 polarization has emerged as a promising strategy for cancer immunotherapy. Polysaccharides are important bioactive substances found in numerous plants, manifesting a wide range of noteworthy biological actions, such as immunomodulation, anti-tumor effects, antioxidant capabilities, and antiviral functions. In recent years, there has been a significant increase in interest regarding the immunomodulatory and anti-tumor properties of polysaccharides derived from plants. The regulatory impact of polysaccharides on the immune system is mainly associated with the natural immune response, especially with the regulation of macrophages. This review provides a thorough analysis of the regulatory effects and mechanisms of plant polysaccharides on TAMs. Additionally, an analysis of potential opportunities for clinical translation of plant polysaccharides as immune adjuvants is presented. These insights have greatly advanced the research of plant polysaccharides for immunotherapy in tumor-related applications.